Factors Influencing Technical Efficiency in Cashew Nut Production - R.K, Koech; P.M, Nyangweso; S.M, Mwakubo (IJRDO - Journal of Business Management, 2016)
The agricultural sector is an important pillar of the coastal economy. Cashew nuts production is widely practiced in Kilifi County. Cashew farming faces several challenges among them pests and diseases. Given a set of inputs, an economic agent will either be efficient or inefficient. There are several factors, both internal and external that may determine the level of operation by a farmer. To determine the factors influencing the technical efficiency level of a farmer a twostage stochastic frontier analysis was done. The first stage generated efficiency scores for each famer which were then regressed against famers characteristics in the second stage. The results of the second stage regression are presented in this paper. The size of the household, gender and availability of extension services were found to positively influence the technical efficiency of a farmer. Gender sensitive policies should therefore be formulated and implemented as a way of assisting farmers attain higher level of efficiency. Intensification of extension service will also see an improvement in farmers’ level of efficiency.